Entrepreneur as an aggrieved party in criminal procedure - Prelińska, Katarzyna (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2016)
The author analyzes the amendment of art. 49 of the Code of Criminal Procedure and presents several aspects of rights granted by the Code of Criminal Procedure to the entrepreneur. The article contains a review of previous problematic provisions of the CCP and describes the new course of reform, which granted the status of aggrieved party to state institutions and local government institutions. The author also emphasizes the role of delivery documents to entrepreneurs as they participate in criminal procedures as an aggrieved party. According to the new art. 304b CCP, written notice of the offense determines not only the elements of the offense but also specifies the identity of the victim by entering the address for correspondence, which in the course of further proceedings allows the authorities to take further procedural steps.